An APETALA2 Homolog, RcAP2, Regulates the Number of Rose Petals Derived From Stamens and Response to Temperature Fluctuations - Han, Yu; Tang, Aoying; Wan, Huihua; Zhang, Tengxun; Cheng, Tangren; Wang, Jia; Yang, Weiru; Pan, Huitang; Zhang, Qixiang (Frontiers in Plant Science, 2018)
Rosa chinensis, which is a famous traditional flower in China, is a major ornamental plant worldwide. Long-term cultivation and breeding have resulted in considerable changes in the number of rose petals, while most wild Rosaceae plants have only one whorl consisting of five petals. The petals of double flowers reportedly originate from stamens, but the underlying molecular mechanism has not been fully characterized. In this study, we observed that the number of petals of R. chinensis ‘Old Blush’ flowers increased and decreased in response to low- and high-temperature treatments, respectively, similar to previous reports. We characterized these variations in further detail and found that the number of stamens exhibited the opposite trend. We cloned an APETALA2 homolog, RcAP2. A detailed analysis of gene structure and promoter cis-acting elements as well as RcAP2 temporospatial expression patterns and responses to temperature changes suggested that RcAP2 expression may be related to the number of petals from stamen origin. The overexpression of RcAP2 in Arabidopsis thaliana transgenic plants may induce the transformation of stamens to petals, thereby increasing the number of petals. Moreover, silencing RcAP2 in ‘Old Blush’ plants decreased the number of petals. Our results may be useful for clarifying the temperature-responsive mechanism involved in petaloid stamen production, which may be relevant for the breeding of new rose varieties with enhanced flower traits.